2021
DOI: 10.1155/2021/6642826
|View full text |Cite|
|
Sign up to set email alerts
|

Consumers’ Perception of Generic Medicines and Evaluation of In Vitro Quality Control Parameters of Locally Manufactured Paracetamol Tablets in Asmara, Eritrea: A Cross-Sectional Study

Abstract: Generic medicines are clinically equivalent and can be used interchangeably for their intended use. Globally, the usage of generic medicines is highly recommended because of their affordability and accessibility. However, consumers hold a negative perception and attitude of using generic medicine as they consider it poor and having inferior quality compared to branded medicines. This study was conducted to assess the consumers’ general view of generic medicines and in vitro evaluation of a locally produced gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…This could be attributed to the ambiguity of their decision and would signify their tendency to change positively their perceptions towards local pharmaceutical products, with some education and support from healthcare professionals. On the other hand, an earlier study conducted in Asmara, Eritrea, reported patients' negative perception about locally manufactured paracetamol and their preference towards the more expensive paracetamol brand, even though laboratory specifications of the local product met the norms (Idris et al 2021).…”
Section: Discussionmentioning
confidence: 91%
“…This could be attributed to the ambiguity of their decision and would signify their tendency to change positively their perceptions towards local pharmaceutical products, with some education and support from healthcare professionals. On the other hand, an earlier study conducted in Asmara, Eritrea, reported patients' negative perception about locally manufactured paracetamol and their preference towards the more expensive paracetamol brand, even though laboratory specifications of the local product met the norms (Idris et al 2021).…”
Section: Discussionmentioning
confidence: 91%
“…Although the quality level of generic drugs is equal to that of original drugs, consumers have perception uncertainty about generic drugs’ quality because they are not aware of the manufacturing process and quality control of generic drugs. 33 , 34 When blockchain technology is used, information about generic drugs’ quality will be effectively disclosed to consumers, thereby updating their perceptions of generic drugs’ quality and changing their purchasing decisions. In this study, we investigate two cases: (1) Case N , which is the case that without blockchain adoption, the quality information of generic drugs will not be disclosed to consumers; (2) Case B , which is the case that with blockchain adoption, the quality information of generic drugs can be known to consumers.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Although generic drugs can be trusted to have the same quality as original drugs based on the FDA, consumers always have risk-aversion and quality uncertainty about generic drugs. 6 According to a cross-sectional study by Idris et al, 7 consumers often perceive generic drugs as inferior in quality compared to branded drugs. The scarcity of information on the manufacturing process and quality control of generic drugs contributes to this untrust.…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled "Consumers' Perception of Generic Medicines and Evaluation of In Vitro Quality Control Parameters of Locally Manufactured Paracetamol Tablets in Asmara, Eritrea: A Cross-Sectional Study" [1], there were errors in Tables 3 and 5, as follows:…”
mentioning
confidence: 99%
“…In the article titled “Consumers' Perception of Generic Medicines and Evaluation of In Vitro Quality Control Parameters of Locally Manufactured Paracetamol Tablets in Asmara, Eritrea: A Cross-Sectional Study” [ 1 ], there were errors in Tables 3 and 5, as follows: In Table 3 , the values included in the percentage column are incorrect due to an error introduced when transferring data from a spreadsheet to statistics software package In Table 5 , there was a typographical error in the last cell in the last row of the percentage column where 1.0657% should be corrected to 106.57% …”
mentioning
confidence: 99%